Peran Media Sosial dan Transformasi Digital dalam Komunikasi Bisnis - Abiem Bagas Saputra; Novri Obaja Pratama; Sarita Diva Aulia; Nur Eka Zahra; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
Digital transformation has fundamentally changed the paradigm of business communication, with social media emerging as a key instrument facilitating the shift from one-way communication to interactive, two-way dialogue. This article aims to analyze the role of social media integration in enhancing customer engagement and strengthening brand image, as well as identifying challenges and drivers in adapting business communication strategies in the digital era. Through a systematic literature review method, this study concludes that social media enables direct, real-time interactions, breaks down geographical boundaries, and serves as a strategic tool for building trust and loyalty. However, its implementation is hampered by ethical challenges such as the risk of misinformation and privacy violations, as well as structural barriers such as rigid organizational hierarchies and incompatible technical systems. On the other hand, changes in consumer behavior, competitive pressures, and external crises are key drivers of the acceleration of digital transformation. The success of social media integration in business communication depends on the synergy between technological capabilities, the development of human digital resource competencies, and an organizational culture that supports innovation and continuous learning.